From PMO to PMOCoE: How Manage Project Knowledge Process Improves Quality of Organization Knowledge Management Assets Cases from UAE - Al-Nakeeb, Ahmed (2024)
Project Management Office Center of Excellence (PMOCoE) is one of the widely used strategies to promote project management as a core competency all over the organization. PMOCoE involves establishing a multidisciplinary team that unites various stakeholder representatives to facilitate the integration of project management disciplines into organizational practices, activities, and processes. For PMOCoE to drive the desired outcomes, it must promote organizational learning to become a "learning organization". This paper presents the fundamentals of PMOCoE, including general requirements, expected outcomes, and the pathways to improved organizational performance, hi this research paper, the data was collected through conducting interviews with projectized entities based in UAE like Dubai Police and the Road and the Transportation Authority in Dubai City. This qualitative data helps to reach the best understanding of the literature review and analysis of some local cases in the UAE. The cases investigated show that the PMOCoE has been used successfully in the UAE. RTA and Dubai police are some of the organizations that have used this concept to improve their overall performance and achieve business growth.